Occurrence of Blastocystis sp. and Pentatrichomonas hominis in sheep and goats in China - Li, Wen Chao; Wang, Kai; Gu, Youfang (Parasites & vectors, 2018)
Global data regarding the molecular epidemiology of Blastocystis sp. and Pentatrichomonas hominis in sheep and goats are sparse. China has one of the largest sheep and goat populations in the world. In this study we investigated the occurrence of Blastocystis sp. and P. hominis in domestic sheep and goats in China, and analyzed the genetic characterization of these two parasite species. In total, we collected fresh fecal samples from 832 sheep and 781 goats located on seven and ten farms, respectively, in the central eastern region of China. The corresponding sequences obtained in this study were subject to molecular analysis for subtype and allele identification of Blastocystis sp., and species and genotype confirmation of P. hominis. The occurrence of Blastocystis sp. was 6.0% (50/832) in sheep and 0.3% (2/781) in goats. The most predominant subtype (ST) of Blastocystis sp. in sheep was ST10 (50.0%), followed by ST14 (20%), ST5 (16%), novel sequence 1 (6%), novel sequence 4 (4%), novel sequence 2 (2%) and novel sequence 3 (2%). However, only ST1 was observed in goats. No mixed infections with different subtypes were found in this study. The 18S alleles showed allele 2 (100%) for ST1; allele 115 (75%) for ST5; and no match allele for ST5 (25%), ST10 (100%), ST14 (100%), novel sequence 1 (100%), novel sequence 2 (100%), novel sequence 3 (100%), and novel sequence 4 (100%) on the Blastocystis subtype (18S) and Sequence Typing (MLST) database. For P. hominis, two goats (0.3%) and zero sheep (0%) were identified as positive in this study. The 18S rRNA gene sequences of two P. hominis isolates from goats displayed 100% identity to type CC1, found previously in dogs, monkeys and humans. These results provide the detailed data on the occurrence and molecular epidemiology of Blastocystis sp. and P. hominis in sheep and goats in China. They also contribute to and expand our knowledge of the Blastocystis sp. and P. hominis epidemiology around the world.